In Vitro and In Vivo Evaluation of Essential Oils Against Sclerotium rolfsii Sacc. - Poudel, Meena Kumari; Shrestha, Sundar Man; Manandhar, Hira Kaji; Yadav, Ritesh Kumar; Subedi, Sujan (Journal of Agriculture and Forestry University, 2025)
Sclerotium rolfsii Sacc., the causal agent of foot rot disease in Capsicum frustescens L. (chilli), is a soil-borne necrotrophic fungal pathogen that leads to significant economic losses. The pathogen’s broad host range and ability to form persistent sclerotia have made it challenging to manage. As an alternative to conventional approaches, botanical and essential oils have been investigated for their disease management potential. In this study, five essential oils were tested in vitro at different concentrations against the pathogen, and only three were chosen for further evaluation in an in vivo experiment on chilli seedlings. The laboratory tests showed that palmarosa and lemon grass completely inhibited mycelial growth of the pathogen at 500 ppm, and at the same concentration, palmarosa, lemon grass, and calamus completely inhibited sclerotial germination. However, none of the tested essential oils were effective against the pathogen in the in vivo test. Despite of having no efficacy in planta assays, the study concluded that the effective essential oils identified in vitro have strong antifungal activity and could be used as an alternative to harmful fungicide. However, more work are warranted for developing proper formulation to maintain their chemical composition in order to manage the disease in vivo conditions.